Projeção e desamparo : filosofia, religião e teoria psicanalítica em Sigmund Freud - Conte, Fabiano Roberto Sales (2009)
One of the most important movements of what we call enlightenment concerns the analysis of the religious phenomenon. Some authors who lived under the aegis of this historical period, as Hume and Feuerbach, adopted a very similar semantics for the construction of their explanatory discourses when dissecting religious belief issues, as well as its motivations and the involved psychical processes. The fear as a cause and the projection as a mental process are important elements in this construction. When Freud who was a reader of both authors and is considered one of the last enlighteners writes some of his texts about the religious phenomenon specifically Totem and Taboo and The Future of an Illusion he ends up making use of explanatory resources which refer to thatphilosophical tradition. The terms which will appear in Freud are helplessness(Hilflosigkeit) and projection(Projektion). These concepts, however, despite of their extreme operativity within the explanatory structure of the religious phenomenon, do not appear for the first time in these cultural texts: they have been part of the history of freudian psychoanalysis for a long time, and have their meaning laboriously built during a long course of development of the theory. The aim of this paper is, thefore, to unravel the paths taken during the elaboration of the concepts of helplessness and projection, so then their real meanings can present themselves when a text on religion is read that will not only allow a more accurate comprehensionabout it but will also demonstrate how the Freudian concepts are developed, both internally in psychoanalysis and in its contact with other forms of construction of knowledge such as philosophy.